From Traditional to Modern: A Bibliometric Analysis of Vocational Education, Collaboration as the Key to Transformation and Quality - Anwari, Hamdan; Sulisworo, Dwi; Widi Pratolo, Bambang (Journal of Vocational Education Studies, 2025)
This study aims to analyze the transformation of vocational education from the traditional approach to the modern model through a bibliometric approach. This study maps the development of research related to vocational education in the one past decade, focusing on publication trends, collaboration between authors, and their relevance to the Sustainable Development Goals (SDGs), especially SDG 4 (Quality Education). Data was obtained from 749 studies analyzed using the PRISMA 2020 method and data visualization such as co-authorship, network, overlay, and density. The results show that digital transformation, technology integration, and collaboration between educational institutions, industry, and the government are the main factors in improving the quality of vocational education. The increase in the number of publications and citations reflects the global attention to curriculum innovation and technology-based learning. This research confirms that multidisciplinary collaboration and adaptation to the needs of the job market are essential to produce a highly qualified workforce. The policy implications of these findings show the need to restructure the vocational curriculum to be in line with the challenges of Industry 4.0 and Society 5.0.